PEMANFAATAN LIMBAH ABUBATU SEBAGAIBAHAN PENGISI DALAM PRODUKSI SELF-COMPACTING CONCRETE - Pusoko Prapto, Siamet Widodo, Agus Santosa (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Abstract limestone powder has been the traditional material used in controlling the segregation potential and deformability of fresh self compacting concrete (SCC). This paper deals with the utilization of alternative materials, such as quarry dust, for SCC applications. This experimental tests aimed to observe the effects of stone dust role in SCC, that utilized by addition and partial replacement ranging from 0%. 12,5% , 25% and 37,5% based on the weight of portland cernent material. The tests were done on compressive strength and splitting tensile strength using three standard cylinder specimens for each data. Test results indicate that stone dust could improve the compressive strength of see by addition method with the optimum dosage in 25°/~ addition by weight of cement, but all test results indicate that stone dust will decrease the splitting tensile strength of see both in addition and partial replacement method. Keywords: self compacting concrete, filler, stone dust. compressive strength, splitting tensile strength.